Neurophysiological Bases of Behavioral Risk Factors for Coronary Heart Disease - Evangeline D. Hayes, Tristan M. Archer (Academic Journal of Clinicians, 2025)
The average normative data on general cerebral indices of human background EEG have been developed and their factor structure has been determined, the functional meaning of general cerebral indices has been established. Stress management techniques, cognitive-behavioral therapy, and changes to one’s lifestyle are examples of behavioral therapies that focus on these neurophysiological reactions. These approaches show promise in lowering the risk of CHD. Knowing how these neurophysiological processes work can help public health and clinical efforts to stop CHD by targeting behavioral risk factors. Health experts can come up with better ways to help people have healthier hearts and lessen the effects of stress and poor behaviors on heart disease by combining psychological and physiological insights. The Purpose of this work is to develop average standard data on general cerebral indices of background EEG in humans, to determine the factor structure of indices and their functional significance as indicators of the degree of psychoemotional activation of the central nervous system, to determine the features of the systemic organization of background EEG in individuals with PTA in a calm state and a state of psychoemotional stress